2000
DOI: 10.1021/es001122u
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and Profiles of Polychlorinated Naphthalene Congeners in Eighteen Technical Polychlorinated Biphenyl Preparations

Abstract: Concentrations and profiles of tri- through octa-chloro-substituted polychlorinated naphthalene (PCN) congeners were determined in eighteen technical polychlorinated biphenyl (PCB) mixtures including Aroclors, Kanechlors, Clophens, Phenoclors, Sovol, and Chlorofen. PCNs were found in all the PCB mixtures at concentrations ranging from 5.2 to 730 μg/g. Concentrations of PCNs in Aroclor and Kanechlor mixtures were greater than those of polychlorinated dibenzofurans (PCDFs) present as impurities in these technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
97
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 34 publications
1
97
0
Order By: Relevance
“…These ratios are obviously different from those of the technical formulations of PCNs and impurities of PCNs in technical formulations of PCBs (ESM Fig. S2; Falandysz et al 2000;Yamashita et al 2000;Noma et al 2004;Falandysz et al 2006a, b). This may provide useful information for identifying specific PCN sources.…”
Section: Profiles Of Emitted Pcnsmentioning
confidence: 83%
See 1 more Smart Citation
“…These ratios are obviously different from those of the technical formulations of PCNs and impurities of PCNs in technical formulations of PCBs (ESM Fig. S2; Falandysz et al 2000;Yamashita et al 2000;Noma et al 2004;Falandysz et al 2006a, b). This may provide useful information for identifying specific PCN sources.…”
Section: Profiles Of Emitted Pcnsmentioning
confidence: 83%
“…The characteristics of PCN profiles from different cataloged sources have been applied to identify the specific source of PCNs in the environment (Schneider et al 1998;Helm and Bidleman 2003;Pan et al 2011). The major sources of PCNs in the environment were the technical formulations of PCNs (such as the Halowax series), industrial thermal processes, and impurities in technical formulations of PCBs (Abad et al 1999;Yamashita et al 2000;Ba et al 2010;Liu et al 2010). Some PCN congeners have been identified that are absent or present in trace amounts in the technical formulations of PCNs and PCBs but are abundant in thermal-related processes (Schneider et al 1998;Helm and Bidleman 2003;Helm et al 2004).…”
Section: Profiles Of Emitted Pcnsmentioning
confidence: 99%
“…Although the production and usage of technical PCN formulations has declined since early 1980s, products containing these formulations are still present in the environment (Kannan et al, 1998). In addition to the release from historical usage of technical formulations, PCNs are also leaked out from impurities of technical PCB preparations and from unlawfully usage in recent years (Falandysz, 1998;Yamashita et al, 2000a). Despite of the phasing out of technical CN formulations, PCNs were detected in sites near chemical industries, such as Chlor-Alkali plants, petrochemical industries, metal refineries, municipal waste incineration plant, and etc (Ba et al, 2010;Brack et al, 2003;Castells et al, 2008;Helm and Bidleman, 2003;Jansson et al, 2008;Kannan et al, 1998;Liu et al, 2010;Llobet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…PCNs were produced for use in capacitor dielectrics, cutting oils, engine oil additives, electroplating stop-off compounds, die casting, ship insulation, wood and paper preservatives, and wire insulation. Production of PCNs in the United States and Europe ceased in the 1980s (Yamashita et al, 2000). PCNs have been reported in incinerator emissions, ambient air, sediment and biota (Harner and Bidleman, 1998;Dö rr et al, 1996;Ishaq et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…PCNs have been reported in incinerator emissions, ambient air, sediment and biota (Harner and Bidleman, 1998;Dö rr et al, 1996;Ishaq et al, 2000). Recently, PCNs have also been detected as impurities of commercial polychlorinated biphenyls (PCBs) (Yamashita et al, 2000). Chlorobenzenes have a wide range of industrial and domestic uses, such as intermediates in the synthesis of other chemicals, solvents, hygiene products, and components of dielectric fluids (Meharg et al, 2000).…”
Section: Introductionmentioning
confidence: 99%